Design of metadata schema for collecting, utilizing and preserving biomechanical data of winter sports experiment - Kim, H.-Y.; Ra, Y.-H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to present metadata elements for managing biomechanical data of winter sports experiments and to establish an Integrated Data Management System with the presented metadata elements. To sort and select metadata elements, metadata crosswalk was done with four internationally used metadata schema; Dublin Core, OECD, DataCite, MODS. And a new metadata schema was designed with common elements from the crosswalk and the metadata elements drawn from general experimental designs and R&D portal. The schema was applied to a research data platform Datanest and the Integrated Management System for experimental data of winter sports was established.